Lived experiences of a Tagasalo having siblings with special needs: An educational implication - Pabatang, Lindy Chielo I.; Naparan, Janus A. (Journal of Educational Management and Instruction (JEMIN), 2023)
Abstract This study focuses on the lived experiences of individuals with siblings with special needs as their tagasalo. It is deeply rooted in Filipino culture and refers to an individual who selflessly takes on the role of a caregiver. This role involves providing support to the family. This study utilized a phenomenological study. An interview guide question was used to gather data. The result of the study showed that the experiences of individuals as tagasalo are challenging. The themes that emerged were Responsibilities of Individuals to their Siblings with Special Needs with the subthemes (1) Assuming the Parental Responsibility from the parents (2) Taking care of their sibling with special needs. Participants’ Support to their Siblings with Special Needs with subthemes (1)Being there for their sibling, (2) Serving as a Defender for their sibling with special needs, (3) Providing Financial Support, (4) Offering Educational Support, Challenges Encountered as Tagasalo of their Sibling with Special Needs with the subthemes (1) Feeling overwhelmed leading to burnout, (2) Facing Additional Financial burden, Managing the encountered challenge with the subthemes (1) Resilience and Spiritual Guidance, (2) Initiative and Proactive Thinking, and Participants insights of Having Siblings with Special Needs were the subtheme such as (11) Developing Self-awareness of Personal growth, (12) Experiencing the Ripple Effects of Personal Development. The tagasalo used their experiences to become better people and responsible individuals. These can provide a safe space to share experiences and emotions.